The language of others, scenario of alterities: Contributions to the theoretical approach between anthropology and literature - Perea, Fabián (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Language, in its multiplicity of action as a mechanism of symbolic reconfiguration, present itself as a constant element in social relations. In this sense, anthropology has questioned not only the usefulness of language in these relationships, but also the way in which it is used within anthropological analyzes and their methodological implications. Literature, on the other hand, is shown as a way in which the use of language responds mainly to a descriptive exercise, which transmutes into the articulation of different symbolic concepts for the creation of a reality in which the author is the architect, which creates relationships between the symbolic reality of the literary author and the abstracted concepts that represent the symbolic organization of specific societies. This review article seeks to explore, through the use of anthropological chronicles and fictional literary texts, the relationships between anthropology and literature from the perspective of language as an element of the creation of otherness, to propose theoretical approaches that question the relationship between the author and the observed subject that, consequently, are presented as possibilities of methodological positions in which language is used as an analytical tool.
Keywords: Literature; anthropology; language; power; symbol; intepretative; relations; otherness